Synthesis of a Cholesterol Side-Chain Triazole Analogue via ‘Click’ Chemistry - Seck, Insa; Fall, Alioune; Lago, Carmen; Sène, Massène; Gaye, Mohamed; Seck, Matar; Gómez, Generosa; Fall, Yagamare (Synthesis, 2015)
An efficient preparation of a cholesterol analogue possessing a triazole ring is achieved starting from commercially available stigmasterol. The procedure is based on a [3+2] cycloaddition of a cholesterol possessing a side-chain terminal azide with a terminal acetylene.
Keywords: triazoles; ‘click’ chemistry; steroids; cholesterol; total synthesis